Construction And Characterization Of A Burkholderia Pseudomallei Wzm Deletion Mutant - Yuen, Chee Wah (2010)
In Burkholderia pseudomallei, a pathogen that causes melioidosis, the gene cluster that encodes for capsular polysaccharide are located in chromosome one. There are 22 genes in this cluster and among the capsular genes in the cluster, the wzm gene has not been studied thoroughly. The amino acid sequence of wzm shows high similarity to CtrC (Neisseria Meningitidis), BexB (Haemophilus Influenzae) and KpsM (Escherichia coli). To study the function of wzm gene, an isogenic mutant of wzm gene was generated and analyzed in comparison with the wild type strain. From the findings, the mutant produced less biofilm compared to the wild type strain. Furthermore, the mutant was more sensitive towards desiccation and oxidative stress than the wild type strain. However, no significant difference was observed for both mutant and wild type strains in their sensitivity towards high osmolarity and acid conditions. Moreover, scanning electron microscopy showed that the bacterial cells of the mutant strain have “rough” surface compared to the wild type strain. However, no phenotypic difference could be observed using transmission electron microscopy when both bacterial cells of both mutant and wild type strains were compared.